Karya Tari Galuik Dantiang Piriang di Era Digital: Kajian Eksistensi - Elfira Rosa Nasution; Yesriva Nursyam; Eva Riyanti; Auliana Mukhti Maghfirah (INDO PUBLISHING, 2026)
This study analyzes how the current digital era significantly influences the way the Galuik Dantiang Piriang dance is recognized, valued, and sustained; it aims to understand how this dance continues to thrive in the digital age. A qualitative research method was employed. Drawing on Jean-Paul Sartre’s theory that